Film and method for producing same
By placing N-methylformamide between two-dimensional particle layers of MXene material, hydrogen bonds are formed to stabilize the interlayer structure, the problem of lower conductivity of MXene material in high temperature and high humidity environment is solved, and the long-term stable performance of the material is achieved .
Patent Information
- Application Number
- CN202380048712.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-20
- Filing Date
- 2023-04-19
- Publication Date
- 2025-02-14
AI Technical Summary
The conductivity of existing MXene materials is prone to decrease in high temperature and high humidity environments, resulting in degradation of performance.
By placing N-methylformamide between the two-dimensional particle layers, hydrogen bonds are formed to stabilize the interlayer structure, inhibit moisture intrusion and interlayer distance expansion, thereby maintaining the stability of conductivity.
It effectively suppresses the reduction of conductivity of MXene materials in high temperature and high humidity environments, ensuring the long-term stable performance of the materials.
Smart Images

Figure CN119451916A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a film and a method for producing the same, and more particularly, to a film containing two-dimensional particles and a method for producing the same. Background Art
[0002] In recent years, MXene has attracted much attention as a new material with electrical conductivity. MXene is a so-called two-dimensional material, and as described later, is a layered material with one or more layers. Generally, MXene has the form of particles (which may include powder, flakes, nanosheets, etc.) of the layered material.
[0003] Currently, various studies are being conducted on the application of MXene in various electrical devices. For example, studies have been conducted to improve the electrical conductivity of materials containing MXene and to expand the application possibilities of materials containing MXene.
[0004] Patent Document 1 describes that the electrical conductivity can be improved by removing the intercalating agent used in the production of MXene through acid treatment.
[0005] In addition, Non-Patent Document 1 describes that MXene is dispersed in a solvent such as N-methylpyrrolidone, dimethyl sulfoxide, dimethylformamide, ethanol, etc. to prepare an ink, and the ink is directly printed on a micro-supercapacitor.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: China Patent Publication No. 112795209
[0009] Non-patent literature
[0010] Non-patent literature 1: Chuanfang (John) Zhang, et al., “Additive-free MXene inks and direct printing of micro-supercapacitors” NATURE COMMUNICATIONS 2019, 10, 1795 Summary of the invention
[0011] Problems to be solved by the invention
[0012] In the MXene described in Patent Document 1 and Non-Patent Document 1, the electrical conductivity may decrease over time.
[0013] An object of the present invention is to provide a film in which the decrease in electrical conductivity over time is suppressed, and preferably to provide a film in which the decrease in electrical conductivity over time is suppressed even under high temperature and high humidity. Another object of the present invention is to provide a method for producing the film.
[0014] Means for solving problems
[0015] The film of the present invention is a film containing two-dimensional particles.
[0016] The two-dimensional particle is a two-dimensional particle having one or more layers, comprising N-methylformamide,
[0017] The above layer comprises the following formula: M m X n The layer body shown and the modification or terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom) present on the surface of the layer body,
[0018] (wherein, M is at least one metal of Groups 3, 4, 5, 6, or 7,
[0019] X is a carbon atom, a nitrogen atom or a combination thereof,
[0020] n is greater than or equal to 1 and less than or equal to 4,
[0021] m is greater than n and less than 5),
[0022] The N-methylformamide is disposed between two adjacent layers.
[0023] The content of N-methylformamide in the film is relative to 1 mol of M m X n It is 0.104 mol or more.
[0024] In addition, the method for producing the film of the present invention comprises:
[0025] (a) Prepare the following formula: M m AX n The precursor steps shown,
[0026] (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7 and contains at least Ti,
[0027] X is a carbon atom, a nitrogen atom or a combination thereof,
[0028] A is at least one element of Group 12, 13, 14, 15, or 16,
[0029] n is greater than or equal to 1 and less than or equal to 4,
[0030] m is greater than n and less than 5);
[0031] (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product;
[0032] (c) a step of cleaning the etched product to obtain an etched and cleaned product;
[0033] (d) a step of mixing the etching and cleaning product and an intercalation agent to obtain an intercalation product;
[0034] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated;
[0035] (f) a step of mixing the delamination product and N-methylformamide to obtain a mixed solution; and
[0036] (h) a step of forming a precursor film using the mixed solution;
[0037] (i) A step of drying the precursor film under normal pressure to form a film.
[0038] Effects of the Invention
[0039] According to the present invention, a film whose conductivity decrease over time is suppressed can be provided, and preferably a film whose conductivity decrease over time is suppressed even under high temperature and high humidity can be provided. In addition, the present invention can provide a method for producing such a film. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is a schematic cross-sectional view showing a MXene particle of a layered material in one embodiment of the present invention, Figure 1 (a) represents a single-layer MXene particle, Figure 1 (b) shows multi-layer (two-layer in the example) MXene particles.
[0041] Figure 2 This is a schematic cross-sectional view showing a film in one embodiment of the present invention. DETAILED DESCRIPTION
[0042] Hereinafter, a film and a method for producing the film according to one embodiment of the present invention will be described.
[0043] The film of the present invention is a film containing two-dimensional particles.
[0044] The two-dimensional particle is a two-dimensional particle having one or more layers, comprising N-methylformamide,
[0045] The above layer comprises the following formula: M m X nThe layer body shown and the modification or terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom) present on the surface of the layer body,
[0046] (wherein, M is at least one metal of Groups 3, 4, 5, 6, or 7,
[0047] X is a carbon atom, a nitrogen atom or a combination thereof,
[0048] n is greater than or equal to 1 and less than or equal to 4,
[0049] m is greater than n and less than 5),
[0050] The N-methylformamide is disposed between two adjacent layers.
[0051] The content of the N-methylformamide in the film is relative to 1 mol of M m X n It is 0.104 mol or more.
[0052] The decrease in conductivity over time of the film of the present invention is suppressed, and preferably the decrease in conductivity over time is suppressed even at high temperature and high humidity. Although it should not be limited to a specific theory, it is considered that in the film of the present invention, a certain amount of N-methylformamide exists between the layers contained in the two-dimensional particles, and the hydrogen bonding group contained in the N-methylformamide can form a hydrogen bond with the modification or terminal T of the layer. Therefore, it can be considered that the above-mentioned N-methylformamide is stably present between the above-mentioned layers, the intrusion of water into the layers is suppressed, and the expansion of the interlayer distance is also suppressed. As a result, it can be considered that the decrease in conductivity caused by the expansion of the interlayer distance can be suppressed.
[0053] In the present invention, when a certain element is referred to as an "atom", the oxidation number of the element is not limited to 0, and may be any number within the range of the oxidation number that the element can take.
[0054] In the present invention, the above two-dimensional particles can be understood as layered materials or layered compounds, also represented as "M m X n T s ", s is an arbitrary number. In the past, x or z was sometimes used instead of s. Typically, n can be 1, 2, 3 or 4, but is not limited thereto.
[0055] In addition, in the present invention, the above-mentioned layer may be referred to as a MXene layer, and the above-mentioned two-dimensional particles may be referred to as MXene two-dimensional particles or MXene particles.
[0056] In the above formula of MXene, M is preferably at least one selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo and Mn, and more preferably at least one selected from Ti, V, Cr and Mo.
[0057] Regarding MXene, the above formula is known: m X n MXene can be represented as follows.
[0058] Sc2C, Ti2C, Ti2N, Zr2C, Zr2N, Hf2C, Hf2N, V2C,
[0059] V2N, Nb2C, Ta2C, Cr2C, Cr2N, Mo2C, Mo 1.3 C.Cr 1.3 C, (Ti, V) 2C, (Ti, Nb) 2C, W2C, W 1.3 C, Mo2N, Nb 1.3 C.Mo 1.3 Y 0.6 C (In the above formula, "1.3" and "0.6" refer to approximately 1.3 (= 4 / 3) and approximately 0.6 (= 2 / 3), respectively.),
[0060] Ti3C2, Ti3N2, Ti3 (CN), Zr3C2, (Ti, V) 3C2, (Ti2Nb) C2, (Ti2Ta) C2, (Ti2Mn) C2, Hf3C2, (Hf2V) C2, (Hf2Mn) C2, (V2Ti) C2, (Cr2Ti) C2, (Cr2V) C2,
[0061] (Cr2Nb)C2, (Cr2Ta)C2, (Mo2Sc)C2, (Mo2Ti)C2,
[0062] (Mo2Zr)C2, (Mo2Hf)C2, (Mo2V)C2, (Mo2Nb)C2, (Mo2Ta)C2, (W2Ti)C2, (W2Zr)C2, (W2Hf)C2,
[0063] Ti4N3, V4C3, Nb4C3, Ta4C3, (Ti, Nb) 4C3, (Nb, Zr) 4C3, (Ti2Nb2) C3, (Ti2Ta2) C3, (V2Ti2) C3, (V2Nb2) C3, (V2Ta2) C3, (Nb2Ta2) C3, (Cr2Ti2) C3,
[0064] (Cr2V2)C3, (Cr2Nb2)C3, (Cr2Ta2)C3, (Mo2Ti2)C3, (Mo2Zr2)C3, (Mo2Hf2)C3, (Mo2V2)C3, (Mo2Nb2)C3, (Mo2Ta2)C3, (W2Ti2)C3, (W2Zr2)C3, (W2Hf2)C3, (Mo 2.7 V 1.3 )C3 (In the above formula, "2.7" and "1.3" refer to about 2.7 (= 8 / 3) and about 1.3 (= 4 / 3), respectively.)
[0065] Typically, in the above formula, M can be titanium or vanadium, and X can be a carbon atom or a nitrogen atom. For example, the MAX phase can be Ti3AlC2, the layer body can be Ti3C2, and the MXene can be Ti3C2T s (In other words, M is Ti, X is C, n is 2, and m is 3).
[0066] It should be noted that in the present invention, MXene may contain a relatively small amount of A atoms from the MAX phase of the precursor, for example, 10% by mass or less relative to the original A atoms. The residual amount of A atoms may preferably be 8% by mass or less, more preferably 6% by mass or less relative to the original A atoms. However, even if the residual amount of A atoms exceeds 10% by mass, there may be no problem depending on the purpose and use conditions of the two-dimensional particles.
[0067] The above two-dimensional particles are composed of Figure 1 The MXene particles 10a (single-layer MXene particles) schematically illustrated in (a) are an aggregate of particles of one layer of MXene (hereinafter referred to as “MXene particles”). More specifically, the MXene particles 10a are MXene layers 7a, and the MXene layers 7a have M m X n The layer body shown (M m X n MXene layer 7a is also represented by “MXene layer 7a”, and the modification or terminal T3a, 5a existing on the surface of the layer body 1a (more specifically, at least one of the two surfaces facing each other in each layer). m X n T s ", s is an arbitrary number. It should be noted that Figure 1 In (a), N-methylformamide is not shown.
[0068] The above two-dimensional particles may include one or more layers. As MXene particles with multiple layers (multilayer MXene particles), such as Figure 1As schematically shown in (b), two layers of MXene particles 10b can be exemplified, but the invention is not limited to these examples. Figure 1 1b, 3b, 5b, 7b in (b) and the above Figure 1 1a, 3a, 5a, and 7a of (a) are the same. Two adjacent MXene layers (e.g., 7a and 7b) of a multilayer MXene particle do not have to be completely separated, but may be partially in contact. The MXene particle 10a is a particle in which the multilayer MXene particles 10b are separated from each other and exist as a single layer. There may be a case where unseparated multilayer MXene particles 10b remain, which is a mixture of the single-layer MXene particles 10a and the multilayer MXene particles 10b. It should be noted that in Figure 1 In (b), N-methylformamide is not shown.
[0069] Without limiting the present embodiment, the thickness of each layer contained in the MXene particle (corresponding to the above-mentioned MXene layers 7a and 7b) is, for example, 0.8 nm to 5 nm, and in particular 0.8 nm to 3 nm (may vary mainly depending on the number of M atomic layers contained in each layer). For each stack of multilayer MXene particles that may be included, the interlayer distance (or gap size, Figure 1 The total number of layers may be 2 or more and 20,000 or less.
[0070] In one embodiment, the two-dimensional particles in the present embodiment preferably include two-dimensional particles with a small number of layers obtained by delamination treatment of the multilayer MXene particles that can be included. The above-mentioned "small number of layers" refers to, for example, the number of stacking layers of MXene layers is less than 6 layers. In addition, the thickness of the multilayer MXene particles with a small number of layers in the stacking direction is preferably less than 15nm, and more preferably less than 10nm. Hereinafter, the "multilayer MXene particles with a small number of layers" are sometimes referred to as "few-layer MXene particles". In addition, single-layer MXene particles and few-layer MXene particles are sometimes collectively referred to as "single-layer·few-layer MXene particles". By including single-layer·few-layer MXene particles, the conductivity of the resulting film can be improved.
[0071] The two-dimensional particles in this embodiment preferably include single-layer MXene particles and few-layer MXene particles, i.e., single-layer and few-layer MXene particles. Among the two-dimensional particles in this embodiment, the proportion of single-layer and few-layer MXene particles with a thickness of 15 nm or less is preferably 90% by volume or more, and more preferably 95% by volume or more.
[0072] In one embodiment, the ratio of (the average value of the major diameter of the two-dimensional surface of the two-dimensional particle) / (the average value of the thickness of the two-dimensional particle) is 1.2 or more, preferably 1.5 or more, and more preferably 2 or more. The average value of the major diameter of the two-dimensional surface of the two-dimensional particle and the average value of the thickness of the two-dimensional particle can be obtained by the method described below.
[0073] (average value of the major diameter of the two-dimensional surface of a two-dimensional particle)
[0074] The average value of the major diameter of the two-dimensional surface of the two-dimensional particle of the present embodiment is 1 μm or more and 20 μm or less. Hereinafter, the average value of the major diameter of the two-dimensional surface may be referred to as “average flake size”.
[0075] The larger the above-mentioned average flake size, the greater the conductivity of the film. The average flake size of the two-dimensional particles of the present embodiment is as large as 1.0 μm or more, so the film formed using the two-dimensional particles, for example, the film obtained by stacking the two-dimensional particles, can achieve a conductivity of more than 2000 S / cm. The average value of the major diameter of the two-dimensional surface is preferably 1.5 μm or more, more preferably 2.5 μm or more. In the case of delamination of MXene by ultrasonic treatment of MXene, most of the MXene is reduced to a major diameter of about hundreds of nm by ultrasonic treatment, so it can be considered that the conductivity of the film formed by the monolayer MXene delaminated by ultrasonic treatment is low.
[0076] From the viewpoint of dispersibility in a dispersion medium, the average value of the major axis of the two-dimensional surface is 20 μm or less, preferably 15 μm or less, and more preferably 10 μm or less.
[0077] As shown in the examples described later, the major diameter of the two-dimensional surface refers to the major diameter when each MXene particle is approximated as an ellipse in an electron microscope photograph, and the average value of the major diameter of the two-dimensional surface refers to the number average of the major diameters of more than 80 particles. As an electron microscope, a scanning electron microscope (SEM) or a transmission electron microscope (TEM) photograph can be used.
[0078] The average value of the major diameter of the two-dimensional particles of the present embodiment can be measured by dissolving a film including the two-dimensional particles in a solvent and dispersing the two-dimensional particles in the solvent. Alternatively, the average value can be measured from a SEM image of the film.
[0079] (Average value of the thickness of two-dimensional particles)
[0080] The average thickness of the two-dimensional particles of this embodiment is preferably 1 nm or more and 15 nm or less. The above thickness is preferably 10 nm or less, more preferably 7 nm or less, and further preferably 5 nm or less. On the other hand, considering the thickness of a single-layer MXene particle, the lower limit of the thickness of the two-dimensional particle may be 1 nm.
[0081] The average value of the thickness of the two-dimensional particles is obtained as a number average size (for example, a number average of at least 40 particles) based on an atomic force microscope (AFM) photograph or a transmission electron microscope (TEM) photograph.
[0082] The above-mentioned two-dimensional particles contain N-methylformamide. N-methylformamide is arranged between two adjacent layers in the two-dimensional particles. Here, the two adjacent layers may be both contained in a single two-dimensional particle having multiple layers, or one of them may be contained in a two-dimensional particle having one or more layers, and the other may be contained in other two-dimensional particles having one or more layers. For example, N-methylformamide may exist on the surface of the two-dimensional particle. That is, N-methylformamide may exist in contact with the layer on the surface side of the layer located on the outermost surface of the two-dimensional particle. Even in this case, it can be considered that N-methylformamide can form hydrogen bonds between the outermost layer of one two-dimensional particle and the outermost layer of other two-dimensional particles, and it can be considered that it can help suppress the decrease in conductivity over time, and further, it can help suppress the decrease in conductivity over time even under high temperature and high humidity.
[0083] Although the explanation should not be limited to a specific theory, it is considered that N-methylformamide has a secondary amino group (-NH-) corresponding to a hydrogen donor and an oxygen atom (O=) corresponding to a hydrogen acceptor as hydrogen bonding groups, and is likely to form hydrogen bonds with the layer modification or terminal T in the above-mentioned two-dimensional particle. Therefore, it is considered that N-methylformamide can stably exist between the layers of the two-dimensional particle, inhibit the intrusion of water into the layers, and maintain the multilayer structure.
[0084] The interlayer distance (d) between the layers of N-methylformamide in the two-dimensional particles can be determined by X-ray diffraction (XRD). 002 ) was measured to confirm. When N-methylformamide exists between the layers of the two-dimensional particles, the interlayer distance (d 002 ) may be, for example, 1.1 nm to 1.5 nm, and further may be 1.2 nm to 1.4 nm. On the other hand, in two-dimensional particles that do not contain enough N-methylformamide, the interlayer distance (d 002 ) can be, for example, greater than 0.8 nm and less than 1.1 nm, which can be distinguished from the above-mentioned two-dimensional particles containing N-methylformamide.
[0085] The above two-dimensional particle (1) and d 002 The half-value width of the corresponding peak in terms of 2θ may be, for example, 0° or more and 0.5° or less, preferably 0° or more and 0.3° or less, and may be 0.1° or more. 002 The half-value width of the corresponding peak is within the above range, and it is estimated that the interlayer distance is uniform.
[0086] The content of N-methylformamide in the film of this embodiment is relative to 1 mol of M m X n The content of N-methylformamide in the film of this embodiment is 0.104 mol or more. Therefore, it is considered that the intrusion of water into the interlayer of the two-dimensional particles can be sufficiently suppressed. m X n The amount may be preferably 0.104 mol or more and 0.5 mol or less, and more preferably 0.12 mol or more and 0.3 mol or less.
[0087] The content of N-methylformamide in the film of the present embodiment can be measured by thermogravimetric analysis (TG). For example, when the temperature is increased from 150°C to 450°C at 10°C / min or 20°C / min, the difference between the mass at 150°C and the mass at 450°C can be taken as the content of N-methylformamide. m X n The amount of substance can be obtained by assuming that the mass before heating to above 150°C is M m X n mass, and divided by M m X n It is calculated by the formula.
[0088] (Embodiment 2: Method for producing two-dimensional particles)
[0089] Hereinafter, a method for producing two-dimensional particles in one embodiment of the present invention will be described in detail, but the present invention is not limited to this embodiment.
[0090] The method for producing two-dimensional particles of this embodiment includes:
[0091] (a) a step of preparing a prescribed precursor;
[0092] (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product;
[0093] (c) a step of cleaning the etched product to obtain an etched and cleaned product;
[0094] (d) mixing the etching and cleaning product with an intercalation agent to obtain an intercalation product; and
[0095] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated,
[0096] (f) By mixing the delaminated product with N-methylformamide, a mixture (slurry) containing the two-dimensional particles can be prepared.
[0097] (g) The above delaminated product may be dried before being mixed with N-methylformamide.
[0098] Hereinafter, each step will be described in detail.
[0099] Process (a)
[0100] First, a predetermined precursor is prepared. The predetermined precursor that can be used in this embodiment is a MAX phase that is a precursor of MXene.
[0101] By the following formula: M m AX n express,
[0102] (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7 and contains at least Ti,
[0103] X is a carbon atom, a nitrogen atom or a combination thereof,
[0104] A is at least one element of Group 12, 13, 14, 15, or 16,
[0105] n is greater than or equal to 1 and less than or equal to 4,
[0106] m is greater than n and less than 5).
[0107] The above-mentioned M, X, n and m are as described above.
[0108] A is at least one element of Groups 12, 13, 14, 15, and 16, usually an element of Group A, representatively Groups IIIA and IVA. More specifically, it may include at least one selected from Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, S, and Cd, preferably Al.
[0109] The MAX phase has a layer composed of A atoms located in the M m X n The MAX phase typically has a repeating unit in the case of m=n+1: one layer of X atoms is arranged between each layer of n+1 layers of M atoms (these layers are also collectively referred to as "M m X n layer”), and configures a layer of A atoms (“A atomic layer”) as a layer next to the layer of the n+1th M atoms, but is not limited to this.
[0110] The MAX phase can be produced by a known method. For example, TiC powder, Ti powder and Al powder are mixed in a ball mill, and the obtained mixed powder is fired in an Ar atmosphere to obtain a fired body (massive MAX phase). Then, the obtained fired body is crushed with an end mill to obtain a powdered MAX phase for the next step.
[0111] Process (b)
[0112] In step (b), etching is performed using an etching solution to remove the precursor M m AX n The etching process removes at least a portion of the A atoms in the precursor. m X n In the state of the layer shown, a processed product can be obtained in which at least a part of the layer composed of A atoms is removed.
[0113] The etching solution may contain an acid such as HF, HCl, HBr, HI, sulfuric acid, phosphoric acid, nitric acid, etc., and typically, an etching solution containing F atoms may be used. Examples of the etching solution include a mixture of LiF and hydrochloric acid; a mixture of hydrofluoric acid and hydrochloric acid; a mixture containing hydrofluoric acid, etc., and these mixtures may further contain phosphoric acid, etc. The etching solution may typically be an aqueous solution.
[0114] As the etching operation and other conditions using the above-mentioned etching solution, the conditions conventionally performed can be adopted.
[0115] Process (c)
[0116] In step (c), the etched product obtained by the etching process is cleaned to obtain an etched and cleaned product. By cleaning, the acid and the like used in the etching process can be sufficiently removed.
[0117] Cleaning can be carried out using a cleaning solution, and typically, can be carried out by mixing the etched material with the cleaning solution. The cleaning solution typically contains water, preferably pure water. On the other hand, in addition to pure water, it can further contain a small amount of hydrochloric acid, etc. The amount of the cleaning solution mixed with the etched material and the mixing method of the etched material and the cleaning solution are not particularly limited. For example, as the mixing method, the etched material and the cleaning solution can be coexisted, stirred, centrifuged, etc. As the stirring method, stirring methods using hand shaking, automatic shakers, shear mixers, pot mills, etc. can be cited. The degree of stirring such as the stirring speed and stirring time can be adjusted according to the amount and concentration of the etched material to be processed. Cleaning with the above-mentioned cleaning solution can be carried out more than once, and preferably multiple cleanings with the cleaning solution are carried out. For example, specifically, the cleaning with the above-mentioned cleaning liquid can be carried out by sequentially performing the following steps: step (i) of adding the cleaning liquid (to the treated material or the remaining precipitate obtained in the following (iii)) and stirring, step (ii) of centrifuging the stirred material, and step (iii) of discarding the supernatant after centrifugation. The steps (i) to (iii) can be repeated in a range of 2 or more times, for example, 15 or less times.
[0118] Process (d)
[0119] In step (d), an intercalation treatment is performed using an intercalation agent to obtain an intercalation-treated product.
[0120] Examples of the intercalant include metal compounds containing metal cations, organic compounds, and organic salts.
[0121] The metal cations may be the same as the metal cations contained in the two-dimensional particles.
[0122] As the above-mentioned metal compound, there can be mentioned an ionic compound formed by bonding the above-mentioned metal cation and an anion. For example, there can be mentioned iodides, phosphates, sulfide salts including sulfates, nitrates, acetates, and carboxylates of the above-mentioned metal cations. As the above-mentioned metal cations, alkali metal ions and alkaline earth metal cations are preferred, and lithium ions are more preferred. As the metal compound, a metal compound containing an alkali metal ion and an alkaline earth metal ion is preferred, a metal compound containing a lithium ion is more preferred, an ionic compound of a lithium ion is further preferred, and one or more of the iodides, phosphates, and sulfide salts of lithium ions are particularly preferred. It can be considered that if lithium ions are used as metal ions, the water hydrated with the lithium ions has the most negative dielectric constant, and therefore it is easy to form a monolayer.
[0123] If a metal compound containing a metal cation is used as an intercalation agent, the metal cation can be intercalated into the etching and cleaning product. m Xn Intercalation treatment between layers.
[0124] The organic compound may be dissolved or miscible in water. The solubility of the organic compound in water at 25° C. is 5 g / 100 g H2O or more, more preferably 10 g / 100 g H2O or more. It should be noted that in this specification, the solubility when miscible with water is considered to be infinite.
[0125] The above organic compound is preferably a highly polar compound. In this specification, the concept of a highly polar compound includes not only compounds that exhibit clear charge separation, but also compounds with high hydrophilicity. The polarity of a compound can be evaluated by using the solubility parameter as an indicator. The Hildebrand solubility parameter (also called "SP value") of the above organic compound is 19.0 MPa. 1 / 2 The SP value of the organic compound is preferably less than the SP value of water, which is 47.8 MPa. 1 / 2 The SP value is a value that serves as an index of the polarity of a compound. The larger the SP value, the higher the polarity. Compounds having similar SP values tend to be compatible with each other.
[0126] The boiling point of the organic compound is, for example, 285° C. or lower, preferably 240° C. or lower, more preferably 200° C. or lower, for example, 50° C. or higher.
[0127] The molecular weight of the organic compound is, for example, 500 or less, preferably 300 or less, more preferably 200 or less, for example, 30 or more.
[0128] Examples of the organic compound include organic compounds having one or more of a carbonyl group, an ester group, an amide group, a formamide group, a carbamoyl group, a carbonate group, an aldehyde group, an ether group, a sulfonyl group, a sulfinyl group, a hydroxyl group, a cyano group, and a nitro group. Specifically, examples of the organic compound include alcohols such as methanol (MeOH), ethanol (EtOH), and 2-propanol; sulfone compounds such as sulfolane; sulfoxides such as dimethyl sulfoxide (DMSO); carbonic acids such as propylene carbonate (PC); amides such as N-methylformamide (NMF), N,N-dimethylformamide, N-methylpyrrolidone (NMP), and dimethylacetamide (DMAc); ketones such as acetone and methyl ethyl ketone (MEK); and tetrahydrofuran (THF).
[0129] If an organic compound is used as an intercalant, the organic compound is intercalated into the etched and cleaned product. m X n The intercalation-treated product of the above-mentioned organic compound is intercalated between the layers.
[0130] Examples of the organic salt include organic salts containing organic cations and anions. Examples of the organic cation include ammonium cations, and examples of the anions include hydroxide ions and chloride ions. Examples of the organic salt include ammonium salts. Specifically, examples of the organic salt include tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH), and tetrabutylammonium chloride.
[0131] If an organic salt is used as an intercalation agent, the organic cations constituting the organic salt can be intercalated into the etching and cleaning processed product. m X n Intercalation treatment between layers.
[0132] The intercalation treatment can be carried out in a dispersion medium. The specific method of the intercalation treatment is not particularly limited. For example, the etching and cleaning treatment product and the metal compound can be mixed and stirred or left to stand. For example, stirring at room temperature can be cited. For example, the above-mentioned stirring method can include a method using a stirrer such as a stirring rod, a method using a stirring blade, a method using a mixer, and a method using a centrifugal device. The stirring time can be set according to the manufacturing scale of the single-layer / few-layer MXene particles, for example, it can be set between 12 and 24 hours.
[0133] The intercalation treatment can be carried out in the presence of a dispersion medium, such as water, organic media such as N-methylpyrrolidone, N-methylformamide, N,N-dimethylformamide, methanol, ethanol, dimethyl sulfoxide, ethylene glycol, acetic acid, etc.
[0134] The order of mixing the dispersion medium, the etching cleaning product and the metal compound is not particularly limited. In one embodiment, the dispersion medium and the etching cleaning product may be mixed before the metal compound is mixed. Typically, the etching solution after etching may be used as the dispersion medium.
[0135] The intercalation treatment can be typically performed on the etched and cleaned product, but in another embodiment, it can also be performed on the above-mentioned precursor simultaneously with the etching treatment. Specifically, the etching and intercalation treatment includes: mixing the precursor, the etching solution and the metal compound containing the metal cation, removing at least a portion of the A atoms from the above-mentioned precursor, and intercalating the metal cations in the precursor from which the A atoms are removed, thereby obtaining the intercalation product. Thus, at least a portion of the A atoms are removed from the precursor (MAX), and the M in the precursor is m X n Layer residue can be obtained in multiple adjacent M m X n Intercalation treatment material with metal cations intercalated between layers.
[0136] As the etching solution and the metal compound used in the etching and intercalation treatment, the same etching solution and the metal compound as used in step (b) can be used, respectively.
[0137] Process (e)
[0138] In step (e), the intercalation product is stirred to perform a delamination treatment to delaminate the intercalation product, thereby obtaining a delaminated product. By this stirring, shear stress is applied to the intercalation product, and two adjacent M m X n At least a portion of the layers can be peeled off, and the MXene particles can be reduced to a single layer or a few layers.
[0139] The conditions for delamination treatment are not particularly limited and can be carried out by known methods. For example, as a method for applying shear stress to the intercalation treated material, a method of dispersing the intercalation treated material in a dispersion medium and stirring can be cited. As a stirring method, stirring using a mechanical shaker, a vortex mixer, a homogenizer, ultrasonic treatment, hand shaking (handshake), an automatic shaker, etc. can be cited. The degree of stirring such as stirring speed and stirring time can be adjusted according to the amount and concentration of the treated material to be treated. For example, after centrifuging the slurry after the above intercalation and discarding the supernatant, pure water is added to the remaining precipitate, and layer separation (delamination) is performed by, for example, hand shaking or stirring with an automatic shaker. The removal of the unpeeled material can be cited as a process of washing the remaining precipitate with water after centrifugation and discarding the supernatant. For example, (i) adding pure water to the remaining precipitate after discarding the supernatant, (ii) centrifugation, and (iii) recovering the supernatant can be cited. The operations (i) to (iii) are repeated once or more, preferably twice or more and 10 times or less, to obtain a supernatant containing single-layer and few-layer MXene particles as a delamination product. Alternatively, the supernatant may be centrifuged, and the supernatant after centrifugation may be discarded to obtain clay containing single-layer and few-layer MXene particles as a delamination product.
[0140] The delaminated product may be further washed before being subjected to the next step.
[0141] In one embodiment, the cleaning can be performed using a cleaning solution, and typically, the cleaning can be performed by mixing the delaminated product with the cleaning solution. In another embodiment, the cleaning can be performed by mixing the acid-treated product with the cleaning solution after subjecting the delaminated product to an acid treatment. As the acid used in the acid treatment, inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, perchloric acid, hydroiodic acid, hydrobromic acid, and hydrofluoric acid; and organic acids such as acetic acid, citric acid, oxalic acid, benzoic acid, and sorbic acid can be appropriately used. The concentration of the acid in the acid solution can be appropriately adjusted according to the delaminated product. In addition, the cleaning using the cleaning solution can be performed by sequentially performing the following steps: step (i) (adding the cleaning solution to the treated product or the remaining precipitate obtained in (iii) below) and stirring, step (ii) centrifuging the stirred product, and step (iii) discarding the supernatant after centrifugation. It can be mentioned that steps (i) to (iii) are repeated within a range of 2 or more times, for example, 15 or less. The stirring can be performed using a hand shaker, an automatic shaker, a shear mixer, a pot mill, or the like. The acid treatment can be carried out more than once. If necessary, the operation of mixing and stirring with a fresh acid solution (an acid solution not used in the acid treatment) can be carried out more than 2 times, for example, less than 10 times. As the above-mentioned cleaning solution, the same cleaning solution as the cleaning solution in the process (c) can be used. For example, specifically, as the cleaning solution, water, preferably pure water, can be used. The above-mentioned mixing can be implemented by the same method as the mixing method in the process (c). For example, specifically, stirring, centrifugation, etc. can be mentioned. As the stirring method, the stirring method using hand shaking, automatic shaking device, shear mixer, pot mill, etc. can be mentioned.
[0142] Process (f)
[0143] In step (f), the delamination product is mixed with N-methylformamide. Thus, N-methylformamide can be inserted between the layers. In step (f), the mixing of the delamination product and N-methylformamide means mixing from a state where the delamination product and N-methylformamide are completely separated to a state where N-methylformamide can exist in the delamination product. For example, the mixing of the delamination product and N-methylformamide can include: a step of stirring the undried delamination product and N-methylformamide; and a step of allowing N-methylformamide to penetrate into the dried delamination product.
[0144] The method of mixing the delaminated material with N-methylformamide is not particularly limited, and known methods can be used. For example, a method of stirring and dispersing N-methylformamide and the delaminated material can be cited. As a stirring method, stirring using a mechanical shaker, a vortex mixer, a homogenizer, ultrasonic treatment, hand shaking, an automatic shaker, etc. can be cited. The degree of stirring such as the stirring speed and stirring time can be adjusted according to the amount and concentration of the material to be processed. In addition, as the above-mentioned mixing method, N-methylformamide can be enumerated to penetrate the dried material of the delaminated material. The penetration can be implemented, for example, by immersing the dried material of the above-mentioned delaminated material in N-methylformamide. In one embodiment, the content of the delaminated material in the mixture containing the delaminated material and N-methylformamide is, for example, 0.5% by mass or more and 10% by mass or less, and can further be 1% by mass or more and 5% by mass or less.
[0145] When the delaminated product is mixed with N-methylformamide, other dispersion medium may coexist. As other dispersion medium, for example, specifically, water may be mentioned. N-methylformamide and other dispersion medium may be mixed in a manner such that the volume ratio of N-methylformamide to other dispersion medium (N-methylformamide / other dispersion medium) is, for example, 50 / 50 or more, preferably 55 / 45 or more.
[0146] Process (g)
[0147] In step (g), the delaminated product may be dried before being subjected to step (f). In this way, water contained in the delaminated product can be removed. Hereinafter, the material obtained by drying the delaminated product is also referred to as a dried product.
[0148] The drying method can be carried out under mild conditions such as natural drying (representatively, placed in an air atmosphere at room temperature and pressure), air drying (blowing air), etc., or under relatively positive conditions such as warm air drying (blowing heated air), heating drying, vacuum drying and / or freeze drying. In step (g), it is preferred to remove the water contained in the delaminated product as much as possible. From this point of view, it is preferred to dry under positive conditions. In addition, in step (g), it is preferred to remove water without heating to a high temperature. For example, the drying temperature in step (g) can be preferably below 190°C, more preferably below 150°C, further below 140°C, and particularly below 120°C. In one embodiment, it can be below 20°C, and further can be below 10°C. From this point of view, as a drying method, vacuum drying and / or freeze drying are preferred, and freeze drying is further preferred.
[0149] In the drying in this step, the dispersion medium can be removed from the delamination treated product, and typically a film-like dried product can be obtained.
[0150] When step (g) is included, the method for producing two-dimensional particles may include, for example:
[0151] (a) a step of preparing a prescribed precursor;
[0152] (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product;
[0153] (c) a step of cleaning the etched product to obtain an etched and cleaned product;
[0154] (d) mixing the etching and cleaning product with an intercalation agent to obtain an intercalation product; and
[0155] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated;
[0156] (g) drying the delamination product to obtain a dried product; and
[0157] (f1) A step of allowing N-methylformamide to permeate into the dried product of the above delamination treatment product.
[0158] In this embodiment, when N-methylformamide is impregnated into the dried delamination product, the amount of the dried delamination product may be, for example, 0.5 to 10 parts by mass, or more, or 1 to 5 parts by mass, relative to 100 parts by mass of N-methylformamide.
[0159] In one embodiment, the content of the two-dimensional particles in the film of the present embodiment is preferably 70% by volume to 100% by volume, more preferably 90% by volume to 100% by volume, and further preferably 95% by volume to 100% by volume.
[0160] In one embodiment, the film of the present embodiment may further include a resin in addition to the two-dimensional particles. Examples of the resin include acrylic resins, polyester resins, polyamide resins, polyimide resins, polyamide-imide resins, polyolefin resins, polycarbonate resins, polyurethane resins, polystyrene resins, polyether resins, polylactic acid, polyvinyl alcohol, and the like.
[0161] In addition, the above-mentioned film may further contain other additives.
[0162] The film manufacturing method in the present embodiment includes the step of forming a film using the two-dimensional particles, and in one embodiment, includes:
[0163] (a) a step of preparing a prescribed precursor;
[0164] (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product;
[0165] (c) a step of cleaning the etched product to obtain an etched and cleaned product;
[0166] (d) a step of mixing the etching and cleaning product with a metal compound containing metal cations to obtain an intercalated product in which the metal cations are intercalated in the etching and cleaning product;
[0167] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated;
[0168] (f) a step of mixing the delamination product and N-methylformamide to obtain a mixed solution; and
[0169] (h) a step of forming a precursor film using the mixed solution;
[0170] (i) A step of drying the precursor film under normal pressure to form a film.
[0171] In another embodiment, the method for manufacturing the film in this embodiment may include:
[0172] (a) a step of preparing a prescribed precursor;
[0173] (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product;
[0174] (c) a step of cleaning the etched product to obtain an etched and cleaned product;
[0175] (d) a step of mixing the etching and cleaning product with a metal compound containing metal cations to obtain an intercalated product in which the metal cations are intercalated in the etching and cleaning product;
[0176] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated;
[0177] (g) drying the delamination product to obtain a dried product;
[0178] (f1) a step of allowing N-methylformamide to permeate into the dried product of the delamination treatment to form a precursor film; and
[0179] (i) A step of drying the precursor film under normal pressure to form a film.
[0180] The mixed solution in the step (f) comprises the delaminated product and / or dried product and N-methylformamide, and may further comprise the resin as required. The formation of the precursor film may be performed, for example, by suction filtering the mixed solution once or twice or more, or by applying the mixed solution and drying it under normal pressure.
[0181] The mixed solution may be applied by spraying, for example, which may be an airless spray method or an air spray method, specifically, a single-fluid nozzle, a two-fluid nozzle, a spray gun, or the like.
[0182] The mixed solution may contain a dispersion medium other than N-methylformamide. As other dispersion medium, for example, specifically, water can be cited. N-methylformamide and other dispersion medium can be mixed in a manner such that the volume ratio of N-methylformamide to other dispersion medium (N-methylformamide / other dispersion medium) is, for example, 50 / 50 or more, preferably 55 / 45 or more.
[0183] In one embodiment, the drying of the precursor film can be carried out at normal pressure. The precursor film comprises two-dimensional particles, N-methylformamide and other dispersion media used as needed. By drying the precursor film, the N-methylformamide contained in the precursor film and at least a portion of other dispersion media that may be contained are removed, and a film can be obtained. The above-mentioned implementation at normal pressure refers to implementation under conditions where no decompression treatment or pressurization treatment is performed. In one embodiment, the normal pressure can be 900 hPa or more and 1,200 hPa or less in absolute pressure, and further, 950 hPa or more and 1,160 hPa or less in absolute pressure. In addition, the drying temperature can be, for example, 190°C or less, preferably 150°C or less, more preferably 140°C or less, further preferably 120°C or less, and further preferably 110°C or less, for example 80°C or more, and preferably 90°C or more. The drying time is, for example, 30 minutes or more and 10 hours or less, and preferably 1 hour or more and 5 hours or less. By drying the dispersion medium under these conditions, a film in which N-methylformamide exists between the layers of the two-dimensional particles can be easily produced.
[0184] As an application of the membrane of this embodiment, an electrode can be mentioned. The electrode only needs to include the above-mentioned membrane, and there is no limitation on the specific form. The electrode can be a solid electrode or a flexible soft electrode.
[0185] In the electrode of this embodiment, the film may be exposed to the outside air so as to be in direct contact with the object to be measured, or may be covered with a substrate and / or a protective film or the like.
[0186] In the case where the electrode of this embodiment has a substrate, the above-mentioned film and the substrate may be in direct contact. The material of the substrate is not particularly limited, and may be, for example, an inorganic material such as ceramics and glass, or an organic material. As the organic material, for example, a flexible organic material may be cited, specifically, a thermoplastic polyurethane elastomer (TPU), a PET film, a polyimide film, etc. may be cited. In addition, the material of the substrate may be a fiber material such as paper, cloth (for example, a sheet-like fiber material).
[0187] The protective layer may be a layer covering at least a portion or all of the film, preferably a layer covering at least a portion of the film. The protective layer may be an organic material, specifically, an acrylic resin, a polyester resin, a polyamide resin, a polyimide resin, a polyamideimide resin, a polyolefin resin, a polycarbonate resin, a polyurethane resin, a polystyrene resin, a polyether resin, polylactic acid, a polyvinyl alcohol or the like.
[0188] The electrodes can be used for any appropriate purpose. For example, they can be used as counter electrodes, reference electrodes, electrodes for electrochemical capacitors, electrodes for batteries, biological electrodes, electrodes for sensors, electrodes for antennas, etc. when performing electrochemical measurements. They can also be used for purposes such as electromagnetic shielding (EMI shielding) that require maintaining high conductivity (reducing the decrease in initial conductivity and preventing oxidation). The details of these uses are described below.
[0189] The electrode is not particularly limited, and may be, for example, a capacitor electrode, a battery electrode, a biosignal sensing electrode, a sensor electrode, an antenna electrode, etc. By using the above-mentioned film, a large-capacity capacitor and battery, a low-impedance biosignal sensing electrode, a highly sensitive sensor and an antenna can be obtained even with a smaller volume (device occupied volume).
[0190] The capacitor may be an electrochemical capacitor. An electrochemical capacitor is a capacitor that utilizes the capacity resulting from the physicochemical reaction between an electrode (electrode active material) and ions (electrolyte ions) in an electrolyte solution, and can be used as a device for storing electrical energy (electrical storage device). A battery may be a chemical battery that can be repeatedly charged and discharged. For example, the battery may be a lithium ion battery, a magnesium ion battery, a lithium sulfur battery, a sodium ion battery, etc., but is not limited thereto.
[0191] The biological signal sensing electrode is an electrode for obtaining biological signals and may be, for example, an electrode for measuring EEG (electroencephalogram), ECG (electrocardiogram), EMG (electromyogram), or EIT (electrical impedance tomography), but is not limited thereto.
[0192] The sensor electrode is an electrode used to detect a target substance, state, abnormality, etc. The sensor may be, for example, a gas sensor, a biosensor (a chemical sensor using a molecular recognition mechanism of biological origin), etc., but is not limited to these.
[0193] The antenna electrode is an electrode used to radiate electromagnetic waves into space and / or receive electromagnetic waves in space. The antenna formed by the antenna electrode is not particularly limited to an antenna for mobile communications represented by mobile phones (so-called 3G, 4G, and 5G antennas), an antenna for RFID, or an antenna for NFC (Near Field Communication).
[0194] The above describes in detail the film and two-dimensional particles in one embodiment of the present invention, but various changes can be made. It should be noted that the film and two-dimensional particles of the present invention can also be manufactured by a method different from the manufacturing method in the above embodiment. In addition, it should be noted that the manufacturing method of the film and two-dimensional particles of the present invention is not limited to providing the film and two-dimensional particles in the above embodiment.
[0195] Example
[0196] The present invention will be described in more detail below with reference to the following examples, but the present invention is not limited to these examples.
[0197] [Example 1]
[0198] [Production of two-dimensional particles]
[0199] In Example 1, the following detailed steps (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, (5) delamination and cleaning, (6) drying, and (7) mixing with N-methylformamide are sequentially performed to produce two-dimensional particles.
[0200] (1) Preparation of precursor (MAX)
[0201] TiC powder, Ti powder and Al powder (all made by Kojun Chemical Research Institute Co., Ltd.) were put into a ball mill equipped with zirconia balls at a molar ratio of 2:1:1 and mixed for 24 hours. The obtained mixed powder was fired at 1350°C for 2 hours under Ar atmosphere. The fired body (block) thus obtained was crushed with an end mill to a maximum size of less than 40μm. Thus, Ti3AlC2 particles were obtained as MAX particles.
[0202] (2) Etching of precursor (ACID method)
[0203] The Ti 3 AlC 2 particles (powder) prepared by the above method were used and etching was performed under the following etching conditions to obtain a solid-liquid mixture (slurry) containing a solid component derived from the Ti 3 AlC 2 powder.
[0204] (Etching conditions)
[0205] Precursor: Ti3AlC2 (passing through a sieve with a mesh size of 45 μm)
[0206] Etching solution composition: 49% HF 6mL
[0207] H2O 18mL
[0208] HCl (12M) 36mL
[0209] Precursor input amount: 3.0g
[0210] Etching container: 100mL bottle container (IBOY)
[0211] Etching temperature: 35°C
[0212] Etching time: 24h
[0213] Stirrer speed: 400rpm
[0214] (3) Cleaning
[0215] The slurry was divided into two parts, each of which was inserted into two 50 mL centrifuge tubes. After centrifugation at 3500G using a centrifuge, the supernatant was discarded. 40 mL of pure water was added to the remaining precipitate in each centrifuge tube, and centrifugation was performed again at 3500G to separate and remove the supernatant. This operation was repeated 11 times. After the final centrifugation, the supernatant was discarded to obtain Ti3C2T x - Moisture medium clay.
[0216] (4) Intercalation
[0217] For the above Ti3C2T s The clay in the water medium was stirred at 20° C. to 25° C. for 12 hours under the following conditions using LiCl as a Li-containing compound to perform Li intercalation.
[0218] (Conditions for Li intercalation)
[0219] Ti3C2T x - Moisture medium clay (MXene after washing): solid content 0.75g
[0220] LiCl: 0.75g
[0221] Pure water: 37.2g
[0222] Intercalation container: 100mL bottle container (IBOY)
[0223] Temperature: 20°C or higher and 25°C or lower (room temperature)
[0224] Duration: 10h
[0225] Stirrer speed: 800rpm
[0226] (5) Delamination and cleaning
[0227] In the above Ti3C2T x - In the water medium clay, (i) 40 mL of pure water was added, and the mixture was stirred with an oscillator for 15 minutes, (ii) centrifuged at 3,500 G, and (iii) the supernatant was recovered as a liquid containing a monolayer MXene. The operations (i) to (iii) were repeated 4 times in total to obtain a supernatant containing a monolayer MXene. Furthermore, the supernatant was centrifuged at 4,300 G for 2 hours using a centrifuge, and the supernatant was discarded to obtain clay containing a delaminated product.
[0228] (6) Drying
[0229] The clay containing the delaminated product was frozen for 16 hours and then freeze-dried for 20 hours to obtain a dried product. The freezing temperature during freezing and freeze-drying was set to -35°C or less, and the pressure during freeze-drying was set to 30 Pa or less.
[0230] (7) Mixture with N-methylformamide
[0231] The dried product and N-methylformamide were mixed so that the content of the dried product in the mixed mixture was 1.5% by mass. Next, the mixture was dispersed for 15 minutes using an ultrasonic cleaner (AS482 manufactured by ASONE) to obtain a slurry containing two-dimensional particles.
[0232] [Film production]
[0233] The slurry was added to a 25 mL syringe and the syringe was placed in a spray coater. Next, a 3 cm square glass substrate (TEMPAX manufactured by SCHOTT) was cleaned with oxygen plasma and placed on a suction stage of the spray coater. The slurry was applied to the cleaned surface and dried with hot air. This operation was repeated 20 times to produce a spray film.
[0234] (Spraying conditions)
[0235] Atomization pressure: 0.5MPa
[0236] Distance between nozzle tip and substrate: 15cm
[0237] ·Liquid delivery volume: 5mL / s
[0238] Scanning speed: 150mm / s
[0239] Stage heater: 100~150℃
[0240] The spray film was dried at 100° C. for 2 hours using a normal pressure oven to prepare a film.
[0241] (Determination of N-methylformamide content)
[0242] In an inert gas atmosphere (He gas atmosphere), a thermogravimetric analyzer (manufactured by NETZSCH) was used to increase the temperature from room temperature to 100°C at a heating rate of 20°C / min. After being kept at 100°C for 10 minutes, the temperature was increased from 100°C to 150°C at a heating rate of 20°C / min. Then, the temperature was increased from 150°C to 450°C at a heating rate of 20°C / min to perform thermogravimetric analysis of the film. The difference between the mass of the film at 150°C and the mass of the film at 450°C was taken as the content of N-methylformamide, and the mass of the film at 450°C was taken as the mass of Ti3C2, and the content (moles) of N-methylformamide relative to 1 mol of Ti3C2 was calculated.
[0243] (Distance between layers(d 002 )
[0244] The interlayer distance (d 002 ) determination.
[0245] (a) The film produced on the above glass substrate was cut into 2 cm squares and XRD measurement was performed using an X-ray diffraction device (manufactured by Rigaku Co., Ltd., SmartLab3 and SmartLab Studio II software) (characteristic X-ray: CuKα 1.541Å), and an XRD curve scanned in the θ-axis direction was obtained in the range of 2θ = 2 degrees to 50 degrees. The step size was set to 0.02 degrees and the scanning speed was set to 5 degrees / minute.
[0246] (b) At around 2θ = 7 degrees, the MXene (Ti3C2T s ), so the peak θ, n = 1, λ = 1.541Å (the wavelength of the CuKα line) is applied to the Bragg formula (2dsinθ = nλ) to find the interplanar spacing d of the (002) plane. 002 The value is used as the distance between layers.
[0247] The interlayer distance was 13.2 Å, which was wider than the interlayer distance (10.9 Å) in the film of Comparative Example 4 produced without using N-methylformamide, confirming that N-methylformamide existed between the layers of the two-dimensional particles included in the film of Example 1.
[0248] (Determination of electrical conductivity)
[0249] The conductivity of the obtained film is determined. Regarding the conductivity, the resistivity (Ω) and thickness (μm) are measured at three locations for one sample, and the conductivity (S / cm) is calculated based on these measured values, and the average value of the three conductivities thus obtained is adopted. In the resistivity measurement, a low-resistance conductivity meter (LorestaAX MCP-T370 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) is used to measure the surface resistance of the film by a four-terminal method. The thickness is measured using a stylus-type surface shape measuring device (DEKTAK8 manufactured by Bruker Japan Co., Ltd.). The thickness immediately before the measurement of the conductivity change described later is taken as the film thickness. Then, the volume resistivity is calculated based on the obtained surface resistance and the film thickness of the film, and the reciprocal of the value is taken to calculate the conductivity, which is set as E0.
[0250] (Determination of conductivity change)
[0251] The film was placed in a constant temperature and humidity chamber at a relative humidity of 85% and a temperature of 60° C. After standing for 1 day, the conductivity was measured and designated as E. E was divided by E0 to obtain the conductivity maintenance rate.
[0252] [Example 2]
[0253] [Production of two-dimensional particles]
[0254] The same procedures as in Example 1 were followed to prepare (1) a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, and (5) delamination and cleaning to obtain a delaminated product. The following step (7) was then performed to produce two-dimensional particles.
[0255] (7) Mixture with N-methylformamide
[0256] 55 parts by volume of N-methylformamide and 45 parts by volume of water were mixed to prepare a mixed dispersion medium, and the delamination treated product and the mixed dispersion medium were mixed so that the content of the delamination treated product in the mixed mixture was 1.5% by mass. Then, the mixture was dispersed for 15 minutes using an ultrasonic cleaning machine (AS482 manufactured by ASONE) to obtain a slurry containing two-dimensional particles.
[0257] [Film production]
[0258] Using the slurry obtained by the above method, a spray film was produced in the same manner as in Example 1. The spray film was dried at 100° C. for 2 hours using a normal pressure oven to produce a film.
[0259] (Determination of N-methylformamide content)
[0260] In an inert gas atmosphere (nitrogen atmosphere), a thermogravimetric analyzer (manufactured by Hitachi High-Tech Science) was used to increase the temperature from room temperature to 100°C at a heating rate of 10°C / min. After being kept at 100°C for 10 minutes, the temperature was increased from 100°C to 150°C at a heating rate of 10°C / min. Then, the temperature was increased from 150°C to 450°C at a heating rate of 10°C / min to perform thermogravimetric analysis of the film. The difference between the mass of the film at 150°C and the mass of the film at 450°C was taken as the content of N-methylformamide, and the mass of the film at 450°C was taken as the mass of Ti3C2, and the content (moles) of N-methylformamide relative to 1 mol of Ti3C2 was calculated.
[0261] (Distance between layers(d 002 )
[0262] The interlayer distance (d 002 ) determination.
[0263] The interlayer distance was 13.0 Å, and it was confirmed that N-methylformamide existed between the layers of the two-dimensional particles included in the film of Example 2.
[0264] (Determination of conductivity and conductivity change)
[0265] In the same manner as in Example 1, the electrical conductivity and the change in electrical conductivity were measured.
[0266] [Example 3]
[0267] [Production of two-dimensional particles]
[0268] The same procedures as in Example 1 were followed: (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, (5) delamination and cleaning, (6) drying, and (7) mixing with N-methylformamide to obtain a slurry containing two-dimensional particles.
[0269] [Film production]
[0270] The slurry obtained by the above method was filtered by suction to prepare a filter membrane. A membrane filter (Durapore, manufactured by Merck, pore size 0.45 μm) was used as the filter for the suction filtration. The filter membrane was dried at 100° C. for 2 hours in a normal pressure oven to prepare a membrane.
[0271] (Determination of N-methylformamide content)
[0272] The M content of N-methylformamide per 1 mol was determined in the same manner as in Example 2. m X n The content (mole) of
[0273] (Distance between layers(d 002 )
[0274] The interlayer distance (d 002 ) determination.
[0275] The interlayer distance was 13.4 Å, and it was confirmed that N-methylformamide existed between the layers of the two-dimensional particles included in the film of Example 3.
[0276] (Determination of conductivity and conductivity change)
[0277] In the same manner as in Example 1, the electrical conductivity and the change in electrical conductivity were measured.
[0278] [Comparative Example 1]
[0279] [Production of two-dimensional particles]
[0280] The same procedures as in Example 1 were followed: (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, (5) delamination and cleaning, (6) drying, and (7) mixing with N-methylformamide to obtain a slurry containing two-dimensional particles.
[0281] [Film production]
[0282] Using the slurry obtained by the above method, a spray film was produced in the same manner as in Example 1. The spray film was dried at 100° C. for 2 hours using a normal pressure oven and then further dried at 150° C. for 16 hours using a vacuum oven to produce a film.
[0283] (Determination of N-methylformamide content)
[0284] The M content of N-methylformamide per 1 mol was determined in the same manner as in Example 2. m X n The content (mole) of
[0285] (Determination of conductivity and conductivity change)
[0286] In the same manner as in Example 1, the electrical conductivity and the change in electrical conductivity were measured.
[0287] [Comparative Example 2]
[0288] [Production of two-dimensional particles]
[0289] The same procedures as in Example 1 were followed: (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, (5) delamination and cleaning, (6) drying, and (7) mixing with N-methylformamide to obtain a slurry containing two-dimensional particles.
[0290] [Film production]
[0291] Using the slurry obtained by the above method, a filtration membrane was produced in the same manner as in Example 3. The filtration membrane was dried in a vacuum oven at 200° C. for 16 hours to produce a membrane.
[0292] (Determination of N-methylformamide content)
[0293] The M content of N-methylformamide per 1 mol was determined in the same manner as in Example 2. m X n The content (mole) of
[0294] (Determination of conductivity and conductivity change)
[0295] In the same manner as in Example 1, the electrical conductivity and the change in electrical conductivity were measured.
[0296] [Comparative Example 3]
[0297] [Production of two-dimensional particles]
[0298] The same procedures as in Example 1 were followed: (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, (5) delamination and cleaning, (6) drying, and (7) mixing with N-methylformamide to obtain a slurry containing two-dimensional particles.
[0299] [Film production]
[0300] Using the slurry obtained by the above method, a filtration membrane was produced in the same manner as in Example 3. The filtration membrane was dried in a normal pressure oven at 100°C for 2 hours and then further dried in a vacuum oven at 150°C for 16 hours to produce a membrane.
[0301] (Determination of N-methylformamide content)
[0302] The M content of N-methylformamide per 1 mol was determined in the same manner as in Example 2. m X n The content (mole) of
[0303] (Determination of conductivity and conductivity change)
[0304] In the same manner as in Example 1, the electrical conductivity and the change in electrical conductivity were measured.
[0305] [Comparative Example 4]
[0306] [Production of two-dimensional particles]
[0307] The same procedures as in Example 1 were followed to carry out (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, (5) delamination and cleaning, and (6) drying to obtain a dried product.
[0308] [Film production]
[0309] A predetermined amount of the dried product was placed in a 50 mL centrifuge tube, and pure water was added. The amount of pure water added was adjusted so that the concentration of the delaminated product in the mixture was 1.5% by mass. The mixture was then stirred with an oscillator for 15 minutes to obtain a slurry.
[0310] Next, the slurry was added to a 25 mL syringe, and the syringe was placed in a spray coater. Next, a 3 cm square glass substrate (TEMPAX manufactured by SCHOTT) was cleaned with oxygen plasma and placed on a suction stage of the spray coater. The slurry was applied to the cleaned surface and dried with hot air. This operation was repeated 20 times to produce a spray film.
[0311] (Spraying conditions)
[0312] Atomization pressure: 0.5MPa
[0313] Distance between nozzle tip and substrate: 15cm
[0314] ·Liquid delivery volume: 5mL / s
[0315] Scanning speed: 150mm / s
[0316] Stage heater: 45°C
[0317] The sprayed film was dried in a normal pressure oven at 80°C for 2 hours, and then further dried in a vacuum oven at 150°C for 16 hours to prepare a film.
[0318] (Determination of N-methylformamide content)
[0319] The M content of N-methylformamide per 1 mol was determined in the same manner as in Example 2. m X n The content (mole) of
[0320] (Distance between layers(d 002 )
[0321] The interlayer distance (d 002 ). The interlayer distance is 10.9 Å.
[0322] (Determination of conductivity and conductivity change)
[0323] In the same manner as in Example 1, the electrical conductivity and the change in electrical conductivity were measured.
[0324] [Comparative Example 5]
[0325] [Production of two-dimensional particles]
[0326] The same procedures as in Example 1 were followed to carry out (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, (5) delamination and cleaning, and (6) drying to obtain a dried product.
[0327] [Film production]
[0328] A predetermined amount of the dried product was placed in a 50 mL centrifuge tube, and pure water was added. The amount of pure water added was adjusted so that the concentration of the delaminated product in the mixture was 1.5% by mass. The mixture was then stirred with an oscillator for 15 minutes to obtain a slurry.
[0329] The slurry was filtered by suction to prepare a filter membrane. A membrane filter (Durapore, manufactured by Merck, pore size 0.45 μm) was used as the filter for the suction filtration. The filter membrane was dried in a vacuum oven at 150° C. for 16 hours to prepare a membrane.
[0330] (Determination of N-methylformamide content)
[0331] The M content of N-methylformamide per 1 mol was determined in the same manner as in Example 2. m X n The content (mole) of
[0332] (Determination of conductivity and conductivity change)
[0333] In the same manner as in Example 1, the electrical conductivity and the change in electrical conductivity were measured.
[0334] N-methylformamide (NMF) was added to 1 mol of M m X n The content, conductivity and conductivity maintenance rate of are shown in Table 1.
[0335] [Table 1]
[0336]
[0337] Examples 1 to 3 are examples of the present invention, and the decrease in conductivity over time was suppressed, and in particular, the decrease in conductivity over time was suppressed even under high temperature and high humidity.
[0338] Comparative Examples 1 to 5 are NMF relative to 1 mol of Mm X n In the case where the content of was less than 0.104 mol, it was confirmed that the electrical conductivity decreased over time.
[0339] The present invention includes the following contents.
[0340] <1>
[0341] A film comprising two-dimensional particles,
[0342] The two-dimensional particle is a two-dimensional particle having one or more layers, comprising N-methylformamide,
[0343] The above layer comprises the following formula: M m X n The layer body shown and the modification or terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom) present on the surface of the layer body,
[0344] (wherein, M is at least one metal of Groups 3, 4, 5, 6, or 7,
[0345] X is a carbon atom, a nitrogen atom or a combination thereof,
[0346] n is greater than or equal to 1 and less than or equal to 4,
[0347] m is greater than n and less than 5),
[0348] The N-methylformamide is disposed between two adjacent layers.
[0349] The content of N-methylformamide in the film is relative to 1 mol of M m X n It is 0.104 mol or more.
[0350] <2>
[0351] The film according to <1>, wherein the layer body comprises Ti 3 C 2 .
[0352] <3>
[0353] A method for manufacturing a film, comprising:
[0354] (a) Prepare the following formula: M m AX n The precursor steps shown,
[0355] (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7 and contains at least Ti,
[0356] X is a carbon atom, a nitrogen atom or a combination thereof,
[0357] A is at least one element of Group 12, 13, 14, 15, or 16,
[0358] n is greater than or equal to 1 and less than or equal to 4,
[0359] m is greater than n and less than 5);
[0360] (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product;
[0361] (c) a step of cleaning the etched product to obtain an etched and cleaned product;
[0362] (d) a step of mixing the etching and cleaning product and an intercalation agent to obtain an intercalation product;
[0363] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated;
[0364] (f) mixing the delamination product with N-methylformamide to obtain a mixed solution; and
[0365] (h) a step of forming a precursor film using the mixed solution;
[0366] (i) A step of drying the precursor film under normal pressure to form a film.
[0367] <4>
[0368] The production method according to <3>, wherein the drying temperature when drying the precursor film is 190° C. or lower.
[0369] <5>
[0370] A method for manufacturing a film, comprising:
[0371] (a) Prepare the following formula: M m AX n The precursor steps shown,
[0372] (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7 and contains at least Ti,
[0373] X is a carbon atom, a nitrogen atom or a combination thereof,
[0374] A is at least one element of Group 12, 13, 14, 15, or 16,
[0375] n is greater than or equal to 1 and less than or equal to 4,
[0376] m is greater than n and less than 5);
[0377] (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product;
[0378] (c) a step of cleaning the etched product to obtain an etched and cleaned product;
[0379] (d) a step of mixing the etching and cleaning product and an intercalation agent to obtain an intercalation product;
[0380] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated;
[0381] (g) drying the delamination product to obtain a dried product;
[0382] (f1) a step of allowing N-methylformamide to permeate into the dried product of the delamination treatment to form a precursor film; and
[0383] (i) A step of drying the precursor film under normal pressure to form a film.
[0384] Description of Reference Numerals
[0385] 1a, 1b: Layer body (M m X n layer)
[0386] 3a, 5a, 3b, 5b: modified or terminal T
[0387] 7a, 7b: MXene layer
[0388] 10, 10a, 10b: MXene particles (two-dimensional particles of layered materials)
Claims
1. A film comprising two-dimensional particles, The two-dimensional particle is a two-dimensional particle having one or more layers, comprising N-methylformamide, The layer comprises the formula: M m X n The layer body shown and the modification or terminal T present on the surface of the layer body, wherein T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom, Formula M m X n Wherein, M is at least one metal of Group 3, 4, 5, 6, or 7, X is a carbon atom, a nitrogen atom or a combination thereof, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5, The N-methylformamide is disposed between two adjacent layers. The content of N-methylformamide in the film is relative to 1 mol of M m X n It is 0.104 mol or more.
2. The film according to claim 1, wherein The layer body contains Ti3C2.
3. A method for producing a film, comprising: (a) Prepare the following formula: M m AX n The precursor steps shown, Formula M m AX n wherein M is at least one metal of Groups 3, 4, 5, 6, and 7 and contains at least Ti, X is a carbon atom, a nitrogen atom or a combination thereof, A is at least one element of Group 12, 13, 14, 15, or 16, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5; (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product; (c) cleaning the etched product to obtain an etched and cleaned product; (d) mixing the etching and cleaning product with an intercalation agent to obtain an intercalation product; (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated; (f) mixing the delamination product with N-methylformamide to obtain a mixed solution; and (h) a step of forming a precursor film using the mixed solution; (i) A step of drying the precursor film at normal pressure to form a film.
4. The manufacturing method according to claim 3, wherein: The drying temperature when drying the precursor film is 190° C. or lower.
5. A method for producing a film, comprising: (a) Prepare the following formula: M m AX n The precursor steps shown, Formula M m AX n wherein M is at least one metal of Groups 3, 4, 5, 6, and 7 and contains at least Ti, X is a carbon atom, a nitrogen atom or a combination thereof, A is at least one element of Group 12, 13, 14, 15, or 16, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5; (b) using an etching solution to remove at least a portion of the A atoms from the precursor, thereby obtaining an etched product; (c) cleaning the etched product to obtain an etched and cleaned product; (d) mixing the etching and cleaning product with an intercalation agent to obtain an intercalation product; (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is delaminated; (g) a step of drying the delamination product to obtain a dried product; (f1) a step of allowing N-methylformamide to permeate the dried product of the delamination treatment to form a precursor film; as well as (i) A step of drying the precursor film at normal pressure to form a film.